1980
DOI: 10.1103/physrevc.22.1857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deformation on neutron total cross sections of even-ANd and Sm isotopes

Abstract: Sm have been measured at 25 energies from 0.75 to 14 MeV. Each sample consisted of about 40 g of powdered oxide with an isotopic enrichment & 94/o.For each isotopic pair the total cross-section difference was determined directly by measuring the ratio of transmitted flux for matched samples. This difference was'found to have an oscillatory behavior when plotted as a function of incident neutron energy. The oscillations have been explained as a deformation effect qualitatively in terms of the nuclear Ramsauer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Our results are discussed below, shown later are Figs. 8 and 10 confirming that calculated total cross sections reproduce the reported experimental data [43][44][45].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Our results are discussed below, shown later are Figs. 8 and 10 confirming that calculated total cross sections reproduce the reported experimental data [43][44][45].…”
supporting
confidence: 80%
“…Cross Section (b) [16,43,44]. Our coupled-channels calculations are divergent below 1 MeV and tend to approach each other above.…”
Section: Incident Neutron Energy (Mev)mentioning
confidence: 99%
See 1 more Smart Citation
“…These data demonstrate that the N = 88 nuclei, 148 Nd and 150 Sm, are weakly deformed. This is confirmed by measurements of total neutron cross sections for the Nd and Sm isotopes [14] and by Coulomb excitation experiments [15]. The N = 88 nuclei with less than 60 protons, that have been investigated using fission fragment spectroscopy, have been suggested as candidates for having a static octupole deformation at medium spins [16][17][18].…”
Section: Introductionmentioning
confidence: 49%
“…It is generally accepted that differences of neutron total cross sections among neighboring nuclei provide an unusually stringent test of optical models [1][2][3][4]. At the same time it has been shown that the standard optical model treatment fails to reproduce the observed differences of total cross sections both for tungsten isotopes [4] and Th-U nuclei [5].…”
Section: Introductionmentioning
confidence: 99%